2022
DOI: 10.3390/d14080650
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Effect of Climate Change on the Distribution of Endemic Anurans from Mexico’s Tropical Dry Forest

Abstract: Mexico is one of the richest countries in amphibian species (420 spp.), with a high level of endemism (69%). The order Anura represents the most diverse and widespread of the three extant amphibian orders (257 spp.). The anurofauna of Mexico’s tropical dry forest ecosystem host a high proportion of the species and endemism registered in the country. In terms of conservation, both dry forests and amphibians are at risk due to climate change because it is expected that as the temperature becomes higher and preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Other than geographic distance, precipitation of the warmest quarter, mean temperature of the wettest quarter, and mean diurnal temperature range best predicted species turnover. Several previous studies have found one or more of these bioclimatic variables to be important in explaining the observed distribution and richness patterns of amphibians (Ballesteros-Barrera et al, 2022;Barrett et al, 2014;Guo et al, 2021). Bioclimatic factors such as precipitation and temperature are especially likely to influence ecological processes and biological functioning in amphibians (Olden & Rooney, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Other than geographic distance, precipitation of the warmest quarter, mean temperature of the wettest quarter, and mean diurnal temperature range best predicted species turnover. Several previous studies have found one or more of these bioclimatic variables to be important in explaining the observed distribution and richness patterns of amphibians (Ballesteros-Barrera et al, 2022;Barrett et al, 2014;Guo et al, 2021). Bioclimatic factors such as precipitation and temperature are especially likely to influence ecological processes and biological functioning in amphibians (Olden & Rooney, 2006).…”
Section: Discussionmentioning
confidence: 98%